Service quality and consumer perception on retail banking facilities and employees’ courtesy in Malaysia and New Zealand - Abdullah, Moha Asri; Abd. Manaf, Noor Hazilah; Ahsan, Kamrul; Azam, S. M Ferdous (EUSEUR Pulishing, 2014)
Service quality and consumer perception are the issues being focused solicitously by the business community today. With the expansion of the banking sector and extensive market formation, scopes of different acuity and satisfaction level for consumers seem to impose a mingle game of their perception on service quality especially in retail banking. However, this study is focused on the service quality and consumer perception on retail banking facilities and employees’ courtesy in Malaysia and New Zealand. For this purpose, a total of 293 respondents participated in this study. Factor analysis was performed to identify the influencing dimensions of service quality, hence revealing two such factors: banking facilities and employees’ courtesy. In order to test the hypotheses vis-à-vis the effect of these two attributes of service quality, structural equation modeling was then employed. The study discovers that while banking facilities exert a significant positive influence on consumer perception, employees’ courtesy does not. The findings of the present study are expected to hold significant implications for the managers in the retail banking sector in enhancing the service quality and customer perception. The findings also expectantly reveal the most obvious implication considering banking service providers to further improve their services quality with greater efficiency and as a way to better compete in the current marketplace. However, few limitations and suggestions for possible future studies are put forward in this regard.